Memórias sobre a UFMG: modernização e repressão durante a ditadura militar - Iara Souto Ribeiro Silva (2017)
The objective of this research is to understand the impact that the Military Dictatorship had on the UFMG, how this period would have been fixed on memory and what are the narratives constructed on the relationship between the university and the military regime and the bodies of surveillance and repression since then. The intention is to shed light on some aspects of the university that were little analyzed to date, perhaps because they are somewhat uncomfortable, or are not consistent with its official memory. I intend to discuss this official memory, which is not necessarily false or untruthful, but it might be incomplete. The memory will be the leitmotif of this work on which I will combine the analysis of mnemonics sources - interviews, publications of memorial character, ephemeris events with that of the documentation produced in the period of dictatorship, like the reports on the Universitys management, reports on the implementation of the university reform at UFMG and documents produced by the information system installed at the university since the creation of the Assessoria Especial de Segurança e Informação (AESI). By means of the analysis of the memories about the University and its relations with the authoritarian regime and its conservative modernization project, I want to ask how a particular conception and narrative about what happened in the past was built and crystallized, what are its senses and what does it serves. For this purpose, I will analyze some of the memory supports, produced at different times, but that, mostly, have in common an understanding of the University as an institution that resisted the authoritarian interference and managed to preserve its autonomy.